Provocation as a Genre: Rhetorical Definitions of MeToo Discourse - Gabrėnaitė, Eglė; Triaušytė, Monika (Respectus Philologicus, 2020)
Modern media has led to changes in the scope, intensity and effectiveness of communication. The Internet medium, which offers almost unlimited dialogue and polylogue possibilities, has become an attractive place for provocation to be born and function. The provocative narrative not only inspires these processes, but also becomes as a result of such a genre modification. This article analyzes a provocative discourse, the Lithuanian version of the global movement MeToo, which promotes the publication of cases of sexual harassment: testimonies of women who have been sexually harassed, publications in the media discussing the issue, interviews with discourse participants, another type of comments. The MeToo discourse is characterized by a rhetorical aspect: the concept of provocation as an effective communication strategy is explored; the relationship of the provocative narrative to the genre category is discussed; characteristic rhetorical elements – invention, disposition, elocution – have been distinguished.